Pre-existing immunity to SARS-CoV-2 before the COVID-19 pandemic era in Cameroon: A comparative analysis according to HIV-status - Aissatou, Abba; Fokam, Joseph; Semengue, Ezechiel Ngoufack Jagni; Takou, Désiré; Ka’e, Aude Christelle; Ambe, Collins Chenwi; Nka, Alex Durand; Djupsa, Sandrine Claire; Beloumou, Grâce; Ciaffi, Laura; Tchouaket, Michel Carlos Tommo; Nayang, Audrey Rachel Mundo; et al. (Frontiers in Immunology, 2023)
Background: The lower burden of COVID-19 in tropical settings may be due to preexisting cross-immunity, which might vary according to geographical locations and potential exposure to other pathogens. We sought to assess the overall prevalence of SARS-CoV-2 antibodies and determine SARS-CoV-2 seropositivity according to HIV-status during COVID-19 pre-pandemic era. Methods: A cross-sectional and comparative study was conducted at the Chantal BIYA International Reference Centre (CIRCB) on 288 stored plasma samples (163 HIV-positive versus 125 HIV-negative) collected before COVID-19 pandemic (2017-2018). On each sample, Abbott PanbioTM COVID-19 IgG/IgM assay was used for detecting SARS-CoV-2 immunoglobulin G (IgG) and M (IgM). Among people living with HIV (PLHIV), HIV-1 viral load and TCD4 cell count (LTCD4) were measured using Abbott Real Time PCR and BD FACSCalibur respectively. Statistical analysis was performed, with p<0.05 considered statistically significant. Results: The median [IQR] age was 25 [15-38] years. Overall seropositivity to SARS-CoV-2 antibodies was 13.5% (39/288) of which 7.3% (21) was IgG, 7.3% (21) IgM and 1.0% (3) IgG/IgM. According to HIV-status, SARS-CoV-2 seropositivity was 11.0% (18/163) versus 16.8% (21/125) among HIV-positive versus HIV-negative respectively, p=0.21. Specifically, IgG was 6.1% (10/163) versus 8.8% (11/125), p=0.26; IgM was 5.5% (9/163) versus 9.6%, (12/125), p=0.13 and IgG/IgM was 0.6% (1/163) versus 1.6% (2/125) respectively. Among PLHIV, SARS-CoV-2 seropositivity according to CD4 count was 9.2% (500 cells/µL) versus 1.8% (200-499 cells/µL), OR 3.5 (p=0.04) and 0.6% (<200 cells/µL), OR 17.7 (p<0.01). According to viral load, SARS-CoV-2 seropositivity was 6.7% (40 copies/mL) versus 4.9% (<40 copies/mL), OR= 3.8 (p<0.01). Conclusion: Before COVID-19 in Cameroon, cross-reactive antibodies to SARS-CoV-2 were in circulation, indicating COVID-19 preexisting immunity. Of relevance, COVID-19 preexisting immunity is lower with HIV-infection, specifically with poor CD4-cell count. Thus, COVID-19 preexisting immunity may contribute in attenuating COVID-19 severity in tropical settings like Cameroon. As poor CD4-count leads to lower cross-reactive antibodies (regardless of viral load), people living with HIV appear more vulnerable to COVID-19 and should be prioritized for vaccination.